TIME OF SERVICE LOGISTICS SYSTEMS TRANSPORTATION COMPANIES (Municipal economy of cities. Series: «Economy science», 2013)
The proposed flowsheet transport service logistics system. The dependence between the time of service of the logistic system and the number of vehicles. The prevailing directions of further research.